ALPHA GLUCOSIDASE INHIBITORY ACTIVITY FROM Syzigium sp. - Saraswaty, Vienna (Teknologi Indonesia, 2010)
Objective of this research is to investigate alpha glucosidase inhibitory activity from Syzygium species. 20 of syzygium species was extracted using 70% ethanol and evaporated to be tested for its alpha glucosidase inhibitory activity and resulted that S. cumini and S. syzygioides have a high alpha glucosidase inhibitory activity with IC50 value was 8.71 ppm and 7.48 ppm respectively. Further investigation on some parts of S. cumini plant showed that the highest activity was found in the cortex with IC50 value of 0.45 ppm. Fractionation of ethanolic extract of S. cumini cortex using n- hexane, dichloromethane, ethyl acetate, n-buthanol and water resulted that the highest yield was in water fraction with IC50 value of 8.15 ppm. Phytochemical screening assay showed that ethanolic extract of S. cumini cortex contained terpenoid, phenol, saponin, tannin and fl avonoid.